Analytic framework for interdisciplinary collaboration in inclusive education. Issue 5 (1st May 2020) - Gerdes, Jantien; Goei, Sui Lin; Huizinga, Mariëtte; de Ruyter, Doret
Abstract : Purpose: The purpose of this paper is to develop an analytic framework for studying interdisciplinary learning in collaboration between schools and child support services. The analytic framework connects the concept of boundary crossing with the social–psychological processes of trust and identity formation. Design/methodology/approach: The paper is written from a theoretical point of view. Empirical research data from two schools are used to illustrate the use and merit of the proposed framework. Findings: The framework proved to be useful for identifying the level of co-work in the two schools. In addition, the framework helped to shed light on how the support for trust and identity formation by the school management aids interdisciplinary learning. Research limitations/implications: The most essential feature of the suggested framework is its use of complex theoretical concepts. Examining each concept in detail would ignore the interconnected nature of concepts in the framework, as well as the fact that it is not yet known how this interconnectedness works. Therefore, the framework is based on a generalised use of the concepts. Practical implications: The contribution of the framework for practice lies in its potential to shed light on how processes in interdisciplinary collaboration can be shaped. The framework can be used to inform contextual interventions that seek to optimize collaborative structures. Originality/value: The paper contributes to understanding the complex processes that constitute interdisciplinary learning in collaboration.